Author Correction: A Donor Quality Index for liver transplantation: development, internal and external validation. Issue 1 (December 2018) - Winter, Audrey; Féray, Cyrille; Audureau, Etienne; Azoulay, Daniel; Antoine, Corinne; Daurès, Jean-Pierre; Landais, Paul
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.